Measured and unmeasured contributions of peer education: experiences from the Get Up, Speak Out for Youth Rights! (GUSO) programme in Kisumu and Siaya Counties, Kenya. Issue 1 (2nd January 2023) - Evelia, Humphres; Watson, Katherine; Billowitz, Marissa; Kivuvani, Mwikali; Amina, Judy; Both, Rosalijn; Araque, Heidy
ABSTRACT: Peer education is a widely used strategy in sexual reproductive health and rights (SRHR) programmes for young people, yet measurement of its effectiveness often focuses on a narrow set of outcomes. This qualitative study explored how peer education was integrated into the Get Up, Speak Out for Youth Rights! (GUSO) programme in Kisumu and Siaya Counties, Kenya and the contribution it made to measured and unmeasured outcomes. Findings indicate that whilst peer educators were a central part of the GUSO theory of change, the intentionality of design varied between partners and sites, and their contributions were formally measured only in relation to two of five outcome areas. In addition to their contributions to these measured outcomes, the study found that peer educators also contributed to a range of other, unmeasured outcomes related to community support and mobilisation; gender norms; and economic empowerment. Findings show that peer educators may contribute to many unmeasured – and sometimes unexpected – outcomes that go beyond traditional measurement of their contributions. These merit further exploration in the literature and in programming. Programme developers are encouraged to be more intentional in the design and measurement of peer education, ensuring that the breadth of its contribution to programming are recognised.